2017
DOI: 10.7166/28-3-1845
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Learning: Skills Development Through Gamification at the Stellenbosch Learning Factory as a Case Study

Abstract: South Africa has a high-cost, low-performance education system, which ultimately leads to unemployment and a skill shortage in the country. In order to bridge the skill shortage gap at a tertiary level, the Stellenbosch Learning Factory (SLF) was established. Learning factories involve experiential learning in a production environment through 'learning by doing'. Gamification, one of the teaching methods used in the SLF, is investigated as a possible answer to South Africa's educational problems. Learning fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Otherwise, virtual LF provide visual software tools trough Virtual Reality (VR) or Augmented Reality (AR) technology [20] to improve Digital LFs. Some LFs have implemented virtual games to evaluate students learning after training [21]. With these technologies, it is possible to carry out digital simulation, simulate tasks or evaluate alternative designs before production start [22].…”
Section: Digital Learning Factories Implementation Trendsmentioning
confidence: 99%
“…Otherwise, virtual LF provide visual software tools trough Virtual Reality (VR) or Augmented Reality (AR) technology [20] to improve Digital LFs. Some LFs have implemented virtual games to evaluate students learning after training [21]. With these technologies, it is possible to carry out digital simulation, simulate tasks or evaluate alternative designs before production start [22].…”
Section: Digital Learning Factories Implementation Trendsmentioning
confidence: 99%
“…A part of the research intended to define the effectiveness of gamification in the educational process is survey based, in which learners were asked to give their assessment of the method. According to the results of these surveys, many students prefer gamification to traditional methods such as lectures (Henning et al 2017). Students assessed positively an educational system which uses game elements.…”
Section: Gamification In Educationmentioning
confidence: 99%
“…Previous research shows that the majority of students prefer the Gamification approach to conventional lecture methods (Henning et al, 2017). It was also found that gamification can support improving metacognitive skills (Tang & Kay, 2014).…”
Section: Introductionmentioning
confidence: 95%